Analysis of Transmission Error of RV Reducer based on Orthogonal Experiment - Li Hui; Xu Honghai; Wu Kai (Jixie chuandong)
The solid assembly model is set up in the Pro / E,and then imported into ADAMS.Based on the orthogonal experimental design with the visual and variance analysis method,the error of the center circle radius of the pin gear,moving distance and the isometric modification of the cycloid gear,the influence of the error of eccentricity and the radius of pin gear on the transmission accuracy are compared and analyzed,and the calculation formula for calculating the transmission error is deduced according to the influence factors.The results show that the error of the center circle radius of the pin gear has the greatest influence on the transmission error of the RV reducer,and the influence of the eccentricity error of the RV reducer is the least.It comparison with the simulation results shows that the calculation formula of transmission error is correct and reliable.